Socioeconomic Characteristics, Nutritional Status, Health Status, and Quality of Life among Tea Plantation Workers in Pangalengan, West Java, Indonesia: English - Puspa, Amalina Ratih; Anwar, Faisal; Khomsan, Ali (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2020)
This cross-sectional study aimed to analyze the association between socioeconomic characteristics, nutritional status, anemia status and health status with the quality of life of tea pickers in Pangalengan, West Java, Indonesia. Subjects were 116 women of childbearing age (15–49) years. Anemia status data (hemoglobin levels) were taken using HemoCue Hb 201+, while nutritional status data were collected through anthropometric measurements (weight and height). Quality of life data was collected using the Short Form-36 (SF-36) questionnaire consisting of the Physical Component Summary (PCS) score and Mental Component Summary (MCS) score. PCS consists of physical function, physical role, pain, and general health dimensions. MCS consists of vitality, social functions, the role of emotions, and mental health. Data were analyzed using a Spearman correlation test, Pearson correlation test, and logistic regression test. The results showed that there was no significant relationship between anemia status and nutritional status with quality of life (p>0.05). However, non-anemic subjects tend to have higher PCS and MCS scores than anemic subjects. There was a positive relationship between Acute Respiratory Infection (ARI) with MCS in terms of social function dimensions, and joint pain with MCS in the emotional role dimension (p<0.05). The variables related to the quality of life were the number of family members and expenditures. Subjects with large family size (≥4 people) had a 3.5 times risk for experiencing lower quality of life compared with subjects with smaller family (<4 people) (OR=3.52; 95% CI:1.23–10.05). Subjects with monthly expense of >Rp. 343,646 had lower risk of experiencing low quality of life 59.7% compared to subjects who had household an expense of <Rp. 343,646 (OR=0.403; 95% CI:0.17–0.96).